2008
DOI: 10.1007/s00277-008-0569-6
|View full text |Cite
|
Sign up to set email alerts
|

The 19-bp deletion of dihydrofolate reductase (DHFR), methylenetetrahydrofolate reductase (MTHFR) C677T, Factor V Leiden, prothrombin G20210A polymorphisms in cancer patients with and without thrombosis

Abstract: Venous thromboembolism (VTE) is a common complication in cancer patients. Several genetic risk factors related to thrombophilia are known; however, their contributions to thrombotic tendency in cancer patients have conflicting results. In the present study, we have focused on the prevalence of methylenetetrahydrofolate reductase (MTHFR) C677T, dihydrofolate reductase (DHFR) 19-bp deletion within intron 1, factor V Leiden (FVL), and prothrombin (PT) G20210A polymorphisms in cancer patients with and without VTE.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 13 publications
1
20
1
Order By: Relevance
“…In 2009, Eroglu et al [9] revealed similar findings. The previous observations could be explained by the fact Thrombophilic gene mutations in cancer Wahba et al 311 that the prevalence of FVL mutation is high among the Turkish population [19].…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…In 2009, Eroglu et al [9] revealed similar findings. The previous observations could be explained by the fact Thrombophilic gene mutations in cancer Wahba et al 311 that the prevalence of FVL mutation is high among the Turkish population [19].…”
Section: Discussionsupporting
confidence: 65%
“…This was proved by other investigators [3,8,9,15,19,20,22]. Although it was reported before that PTH G20210A gene mutation appeared to be a risk factor for thrombosis among patients with nonhematological malignancy.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…A C-T polymorphism at nucleotide 677 in the MTHFR gene leads to increased levels of homocysteine, which is a risk factor for thrombosis (8). The other most extensively investigated thrombosis-related factors are FVL and PTH.…”
Section: Introductionmentioning
confidence: 99%